Phytophthora infestans RxLR Effector PITG06478 Hijacks 14-3-3 to Suppress PMA Activity Leading to Necrotrophic Cell Death - Ye-Eun Seo; Xin Yan; Doil Choi; Hyunggon Mang (Molecular Plant-Microbe Interactions, 2023)
Pathogens often induce cell death for their successful proliferation in the host plant. Plasma membrane H+-ATPases (PMAs) are targeted by either pathogens or plant immune receptors in immune response regulation. Although PMAs play pivotal roles in host cell death, the molecular mechanism of effector-mediated regulation of PMA activity has not been described. Here, we report that the Phytophthora infestans RxLR effector PITG06478 can induce cell death in Nicotiana benthamiana but the induced cell death is inhibited by fusicoccin (FC), an irreversible PMA activator. PITG06478, which is localized at the plasma membrane, is not directly associated with the PMA but is associated with Nb14-3-3s, a PMA activator. Immunoblot analyses revealed that the interaction between PITG06478 and Nb14-3-3s was disrupted by FC. PMA activity in PITG06478-expressing plants was eventually inhibited, and cell death likely occurred because the 14-3-3 protein was hijacked. Our results further confirm the significance of PMA activity in host cell death and provide new insight into how pathogens utilize essential host components to sustain their life cycle. [Graphic: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.